2018
DOI: 10.1097/ajp.0000000000000565
|View full text |Cite
|
Sign up to set email alerts
|

The Pain Course

Abstract: These findings highlight the potential value of internet-delivered programs when provided by specialist pain management clinics as a part of their services and the value of larger scale studies in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Effectiveness studies of internet-delivered psychological interven-improvements on self-efficacy, activity engagement, pain intensity, pain interference, and treatment satisfaction (Sullivan et al, 2018). Another uncontrolled trial of IACT provided in a tertiary care setting (n = 39) showed significant improvements on depression, anxiety, and disability for a subgroup of participants (Dear et al, 2018). In addition, a wait-list control trial on IACT for chronic pain patients in tertiary care (n = 113), although self-referred, showed treatment effects on pain interference, depression, anxiety, pain intensity, and insomnia (Rickardsson et al, 2021).…”
Section: Internet-delivered Acceptance and Commitment Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Effectiveness studies of internet-delivered psychological interven-improvements on self-efficacy, activity engagement, pain intensity, pain interference, and treatment satisfaction (Sullivan et al, 2018). Another uncontrolled trial of IACT provided in a tertiary care setting (n = 39) showed significant improvements on depression, anxiety, and disability for a subgroup of participants (Dear et al, 2018). In addition, a wait-list control trial on IACT for chronic pain patients in tertiary care (n = 113), although self-referred, showed treatment effects on pain interference, depression, anxiety, pain intensity, and insomnia (Rickardsson et al, 2021).…”
Section: Internet-delivered Acceptance and Commitment Therapymentioning
confidence: 99%
“…So far, ICBT for chronic pain has been successfully delivered without tailored treatment (Buhrman et al, 2016) (Dear et al, 2018), although tailoring could potentially affect motivation, adherence and satisfaction rather than outcomes (Martorella et al, 2017). For example, matching treatment format with patients' expectation, requests and characteristics could enhance adherence (Gasslander et al, 2021).…”
Section: Tailored Treatmentmentioning
confidence: 99%
“…Individualized guidance might help patients gain from pivotal interventions [7]. However, ICBT for chronic pain has so far been successfully delivered without individual adjustments [11,19]. Tailored treatment is relevant when there is a variation in symptoms or consequences, or when pain is one of comorbid syndromes [4].…”
Section: Introductionmentioning
confidence: 99%